Formação de professores para inclusão de pessoas com deficiência intelectual : análise de um currículo de licenciatura em Educação Física - Borges, Everton Cardoso (2016)
According to current legislation, children with special needs, regardless of their disability, should be included in basic education. Implying that have human development opportunities. More than a requirement, this legal provision is a conquered right. After almost twenty years after the adoption of the legislation, one wonders: the initial training courses for teachers are preparing future teachers to work in the development of students with intellectual disabilities? As the degrees are organizing their curricula in order to give teachers the necessary knowledge to human development of people with intellectual disabilities? With these questions, we undertook to carry out a survey of the curriculum of a course of initial training of physical education teachers to work in basic education in order to identify training processes from the perspective of inclusion and contribute to the definition of theoretical support and practical necessary to course curriculum and to prepare them to contribute to the realization of the human development of students with intellectual disabilities. Thus, the delimitation of the research was carried out on a course of degree in Physical Education in the city of Pontal do Araguaia / MT, operating in a Higher Education Institution (HEI) federal public. The overall objective of the research was to analyze and reflect the curriculum policy Degree in Physical Education, with regard to training for the inclusion of people with intellectual disabilities in Basic Education. For understanding the study object was used authors who discuss teacher training, curriculum ideas and the theme of Special Education. We opted for the qualitative research approach, trying to descriptions and interpretations of the documents reviewed, interviews with teachers and students of the course of IES selected for the research. Data collection occurred by documents, interviews and questionnaires. The analysis was to demonstrate features, descriptions and relationships established in the studied phenomenon in order to get answers to the questions identified in the survey. The data indicate that the research institution offers the curriculum disciplines pounds and Adapted Physical Education, but they do not achieve the objective of this study is that students with intellectual disabilities. Based on the foregoing, we arrive at the conclusion that the course curriculum researched the initial teacher training is directed to the education of people with special educational needs in general terms, not delimiting its specificity, students with intellectual disabilities. It notes that this initial training at some point will be weakened. It is noted also that the lack of studies on the intellectual deficient in physical education in undergraduate course curriculum can be considered one of the factors that hinder the inclusion of all students in basic education.